Association Between Parental Marital Status and Types of Suicidal Behavior Among Korean Adolescents: A Cross-sectional Study - Yoon Sik Park; Eun-Cheol Park (Korean Society for Preventive Medicine, 2020)
Objectives Adolescent suicide is a global problem. This study aimed to identify associations between parental marital status and suicidal behavior. Methods This study analyzed 118 715 middle and high school students from the 13th and 14th Korea Youth Risk Behavior Web-based Survey. The odds ratios (ORs) of suicidal ideation, planning, and attempts were calculated based on parental marital status, living situation, and socioeconomic factors. The data were analyzed using multiple logistic regression. Results When compared to those living with 2 married biological parents, the ORs of suicidal ideation among adolescents living with either remarried or no parents were 1.34 (95% confidence interval [CI], 1.17 to 1.53) and 1.36 (95% CI, 1.11 to 1.66), respectively. For suicidal planning, the OR of those living with 1 remarried biological parent was 1.24 (95% CI, 1.01 to 1.52), and that of those living without parents was 1.28 (95% CI, 0.95 to 1.73), when compared to adolescents living with 2 married biological parents. For suicide attempts, when compared to adolescents with 2 married biological parents, the OR of those living with 1 remarried biological parent was 1.48 (95% CI, 1.17 to 1.87) and that of those living without parents was 2.02 (95% CI, 1.44 to 2.83). For adolescents living with 1 remarried biological parent, suicidal behavior was strongly associated with having no siblings and were weakly associated with not living with grandparents. Conclusions Suicidal behavior among adolescents was associated with the remarriage and loss of parents. Therefore, special attention and interventions are needed for adolescents in those situations.